In vitro Evaluation of Antioxidant Activity of Iranian Mentha longifolia Essential Oil and Extracts - A Kamkar; N Shariatifar; AH Jamshidi; A Jebelli Javan; T Sadeghi; MM Zeagham Monfared (Institue of Medicinal Plants, ACECR, 2012)
Background: The antioxidant properties of medicinal plants as natural resources are located attention by researchers for use in food and biological systems .   Objectives: The purpose of this study was to evaluate antioxidant activity of essential oil and extracts of Mentha longifolia as asubstitute for synthetic antioxidants.   Methods: In this laboratory study , the essential oil plant was analyzed by GC / MS. Antioxidant activity of essential oil and extracts was evaluated with DPPH free radical scavenging and beta-carotene bleaching methods and was compared with synthetic antioxidant BHT.   Results: The major components of Mentha longifolia essential oil were monoterpen oxygen compounds including Cis-piperitone epoxide %28.23, Alpha-terpineol %18.64, Menthone % 10.97 , Pulegone %9.73 and Cis-piperitone epoxide %8.73 . IC50 of Mentha longifolia essential oil was 1765 ± 5 μg / ml and IC50 of aqueous, ethanolic and methanolic extracts were 100 ± 1.2, 53.8 ± 0.58, 50 ± 0.5 , while IC50 of BHT was 4.9 ± 0.25 μg / ml . furthermore, in beta-carotene bleaching method, the antioxidant activity essential oil was 60 percent and IC50 of aqueous, ethanolic and methanolic extracts were estimated73.27,89.88, 84.79 percent respectively . while parameters for BHT 95 ± 0/9 percent. Conclusion: The antioxidant properties of essential oil tested was not significant, while the extracts showed considerable antioxidant properties that candidate them for using in foods as a natural antioxidant.